Optimization of tax revenue in East Java: an empirical analysis of Spatial Durbin Error Model. Issue 1 (May 2021) - Afifah, D L; Rahardjo, S; Kusumasari, V; Atikah, N; Kholifia, N
Abstract: Data containing spatial effects should be analyzed using a spatial model. One of the spatial models is Spatial Durbin Error Model (SDEM). In the SDEM model, the independent variable and error both contain spatial effects. Along with the implementation of regional autonomy, each region is given the freedom to regulate financing. Each area tries to explore their respective potential to get a large Regional Original Income. Taxes are an essential source of the regional revenue so that local governments try to optimize tax revenue. This paper empirically examines the factors that can maximize tax revenue in East Java and maps the potential areas to generate high taxes. Some of the factors considered include Gross Regional Domestic Product (GRDP), population, per capita income, number of industries. By using the SDEM model, it can be seen that there is a spatial relationship, where the amount of tax revenue in each region is different and is influenced by other areas.